Pengaruh Penambahan Konsentrasi Jus Jambu Biji Merah (Psidium guajava L.) terhadap Kadar Asam Laktat, Vitamin C, dan Akseptabilitas Set Yogurt - Muhamad Raihan Aufa; Wendry Setiyadi Putranto; Roostita Lobo Balia (Unpad Press, 2020)
Red guava has high level of vitamin C, so it can be used as a source of vitamin C, also has a distinctive color. This study aims to determine the effect with different concentration of guava juice on lactic acid levels, vitamin C and acceptability of cow milk yogurt set. The experimental method used Completely Randomized Design (CRD) with four treatments increasing the concentration of red guava juice (0%, 5%, 10%, and 15%) and each treatment repeated five times. The results showed that the addition of the concentration of red guava juice by 0% to 15%, the lactic acid levels of different cow’s milk set yogurts showed a negative linear regression pattern with the regression y = -0,03724x + 1,10465 R² = 0,99699, and increasing vitamin C levels following a positive linear regression pattern y = 1,2932x – 0,324 R² = 0,9452. The concentration of red guava juice 15% produced the best cow’s milk set yogurt with 0,55% lactic acid levels and 20,69 mg/100 g vitamin C levels produces and produced the most preferred acceptability value with hedonic scale likes and numeric scales 2,20.